Modelling of an intermediate pressure microwave oxygen discharge reactor: from stationary two-dimensional to time-dependent global (volume-averaged) plasma models. (2nd October 2015) - Kemaneci, Efe; Carbone, Emile; Jimenez-Diaz, Manuel; Graef, Wouter; Rahimi, Sara; van Dijk, Jan; Kroesen, Gerrit
Abstract: A microwave-induced oxygen plasma is simulated using both stationary and time-resolved modelling strategies. The stationary model is spatially resolved and it is self-consistently coupled to the microwaves (Jimenez-Diaz et al 2012 J. Phys. D: Appl. Phys .45 335204), whereas the time-resolved description is based on a global (volume-averaged) model (Kemaneci et al 2014 Plasma Sources Sci. Technol. 23 045002). We observe agreement of the global model data with several published measurements of microwave-induced oxygen plasmas in both continuous and modulated power inputs. Properties of the microwave plasma reactor are investigated and corresponding simulation data based on two distinct models shows agreement on the common parameters. The role of the square wave modulated power input is also investigated within the time-resolved description.